Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.2147/dddt.s396649
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanism of Qianshan Huoxue Gao in Acute Coronary Syndrome via Regulation of Intestinal Flora and Metabolites

Abstract: Purpose To study the efficacy of Qianshan Huoxue Gao (QS) in treating acute coronary syndrome (ACS) and to explore the mechanism of action from the perspective of intestinal flora regulation. Methods Male Sprague–Dawley rats were divided into control, model, QS, and atorvastatin groups; except for the control group, rats underwent ligation of the left anterior descending branch of the coronary artery. Following treatment for 28 days, cardiac function was evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Certain bacteria influence bone metabolism by mediating inflammation. Oscillospiraceae unclassified was negatively correlated with cellular inflammatory factors (IL-6, TNF-α, MCP-1) ( 79 ); UCG-005 was inversely associated with the expression of pro-inflammatory cytokines (IL-12, IL-11, IL-8, IL-6, TNF-α, IL-1β and MCP-1) ( 80 82 ); Lachnospiraceae _NK4A136_group was inversely associated with the expression of cellular inflammatory factors (IL-1β, TNF-α, PGE-2, IL-6, and IFN-γ) ( 83 85 ); Desulfovibrionaceae unclassified was positively correlated with the expression of cellular inflammatory factors (TNF-α, IL-6, IL-1β, and MCP-1) ( 86 , 87 ). A large increase in pro-inflammatory cytokines can act directly or indirectly on osteoblasts or osteoclasts, promoting the differentiation of monocytes into mature osteoclasts, increased bone resorption, and decreased bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Certain bacteria influence bone metabolism by mediating inflammation. Oscillospiraceae unclassified was negatively correlated with cellular inflammatory factors (IL-6, TNF-α, MCP-1) ( 79 ); UCG-005 was inversely associated with the expression of pro-inflammatory cytokines (IL-12, IL-11, IL-8, IL-6, TNF-α, IL-1β and MCP-1) ( 80 82 ); Lachnospiraceae _NK4A136_group was inversely associated with the expression of cellular inflammatory factors (IL-1β, TNF-α, PGE-2, IL-6, and IFN-γ) ( 83 85 ); Desulfovibrionaceae unclassified was positively correlated with the expression of cellular inflammatory factors (TNF-α, IL-6, IL-1β, and MCP-1) ( 86 , 87 ). A large increase in pro-inflammatory cytokines can act directly or indirectly on osteoblasts or osteoclasts, promoting the differentiation of monocytes into mature osteoclasts, increased bone resorption, and decreased bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…g_unclassified_f_Oscillospiraceae and g_NK4A214_group are also dominant bacteria in ALI in mice after propolis pretreatment, which all belong to the o_Oscillospirales. o_Oscillospirales have a strong connection with human health, can produce SCFAs, and may be representative of the next generation of beneficial bacteria [ 52 ]. In the tree gum pretreatment group, f_Bacillaceae and g_Pseudogracilibacillus belonging to o_Bacillales were the dominant microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang Ling et al found that butyrate could be protective against cardiac metabolic disorders in T2DM mice [ 30 ]. Previous studies have shown a correlation between CK-MB levels and glucose levels [ 31 ]. The present study also identified a negative correlation between Romboutsia and Roseburia with both FPG and CK-MB levels.…”
Section: Discussionmentioning
confidence: 99%